2018
DOI: 10.1111/oik.05697
|View full text |Cite
|
Sign up to set email alerts
|

Litter type and termites regulate root decomposition across contrasting savanna land‐uses

Abstract: Decomposition is a vital ecosystem process, increasingly modified by human activity. Theoretical frameworks and empirical studies that aim to understand the interplay between human land‐use, macro‐fauna and decomposition processes have primarily focused on leaf and wood litter. For a whole‐plant understanding of how land‐use and macro‐fauna influence decomposition, investigating root litter is required. Using litterbags, we quantified rates of root decomposition across contrasting tropical savanna land‐uses, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…However, prior work in the Serengeti found that termites eat through nylon litterbags to access plant litter creating holes~0.55 mm 2 in size (Smith et al 2019). To quantify the contributions of macrodetritivores to litter decomposition, we used a stainless steel metal mesh treatment with an aperture size of 0.3 mm designed to exclude the head-width of the smallest foraging termites (Smith et al 2019;Teo et al 2020). Our litterbag approach targeted termites, but could equally apply to other savannah macrodetritivores with strong mandibles such as beetle larvae, millipedes and woodlice.…”
Section: Experimental Designmentioning
confidence: 99%
See 4 more Smart Citations
“…However, prior work in the Serengeti found that termites eat through nylon litterbags to access plant litter creating holes~0.55 mm 2 in size (Smith et al 2019). To quantify the contributions of macrodetritivores to litter decomposition, we used a stainless steel metal mesh treatment with an aperture size of 0.3 mm designed to exclude the head-width of the smallest foraging termites (Smith et al 2019;Teo et al 2020). Our litterbag approach targeted termites, but could equally apply to other savannah macrodetritivores with strong mandibles such as beetle larvae, millipedes and woodlice.…”
Section: Experimental Designmentioning
confidence: 99%
“…or on the diets of insectivorous mammals, for example aardwolf consumption of Trinervitermes spp. termites (de Visser et al 2015;Freymann et al 2008;Freymann et al 2007;Freymann et al 2010;Kruuk and Sands 1972;Smith et al 2019). Inside wildlife protected areas, the majority of wild herbivores (including elephants, buffalos, impalas and various species of antelope) occur at low densities, with the exception of migratory wildebeest and zebra (Hopcraft et al 2015;Sinclair et al 2007).…”
Section: Study Area and Site Selectionmentioning
confidence: 99%
See 3 more Smart Citations